Criteria for the regularity of growth of the logarithm of modulus and the argument of an entire function - Bodnar, O. V.; Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For entire functions whose zero counting functions are slowly increasing, we establish criteria for the regular growth of their logarithms of moduli and arguments in the metric of L^p [0, 2π].